Metallothionein expression in colorectal cancer: Relevance of different isoforms for tumor progression and patient survival - Arriaga, Juan Martín (2012)
Metallothioneins are a family of small, cysteine-rich proteins with many functions. Immunohistochemical evaluation of all metallothionein 1 + 2 isoforms in colorectal tumors has demonstrated an important down-regulation compared with normal tissue, although its prognostic significance is unclear. Moreover, the contribution of individual isoforms to overall metallothionein down-regulation is not known. To address these important issues, we analyzed the messenger RNA expression levels of all functional metallothionein 1 + 2 isoforms by quantitative reverse transcription polymerase chain reaction in 22 pairs of normal and tumor-microdissected epithelia and correlated these to the overall immunohistochemical protein expression. Our results showed that 5 isoforms (MT1G, 1E, 1F, 1H, and 1M) were lost during the transition from normal mucosa to tumor, whereas MT1X and MT2A were less down-regulated, and their expression was correlated with overall protein positivity. Second, we showed that MT1G hypermethylation occurred in cell lines and in 29% of tumor samples, whereas histone deacetylase inhibitors are able to induce most isoforms. Furthermore, we analyzed by immunohistochemistry 107 normal mucosae, 25 adenomas, 81 carcinomas, and 19 lymph node metastases to evaluate metallothionein expression during different stages of cancer development and to assess its relationship to patient survival. A lower immunohistochemical expression was associated with poorer survival, although it was not an independent predictor. Overall, this study identifies for the first time the relevant metallothionein isoforms for colorectal cancer progression, supports the concept that their loss is associated with worse prognosis, and suggests 2 mechanisms for epigenetic repression of metallothionein expression in colorectal tumors.